Fusion of Weakly-Bound ⁹Be With Heavy Nuclei ²⁰⁸PB: A Multi-Body Three-Stage Classical Molecular Dynamics Approach - Katariya, Vipul B.; Patel, Jignasha A.; Mahida, Hardip R.; Jariwala, Pinank H. (East European Journal of Physics, 2026)
The fusion of the weakly bound 9Be nucleus with 208Pb is investigated using a multi-body three-stage classical molecular dynamics (3S-CMD) approach. This model explicitly treats 9Be as a cluster of 4He and 5He, allowing for the relaxation of rigid-body constraints on both projectile fragments and the target. In this paper, the influence of these constraints on the complete fusion (CF) cross-section, considering both central and non-central collisions is studied. Systematic removal of rigidity constraints, particularly on the target and the 9Be fragments, significantly affects the CF cross-section, especially at sub-barrier energies. Calculations show that relaxing these constraints enhances CF, indicating the important role of breakup and internal degrees of freedom. The multibody 3S-CMD model provides a tool for understanding the interplay of breakup and fusion in reactions involving weakly bound nuclei.